2021
DOI: 10.3390/ijms222111945
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Tolerance and Autoimmunity as Missing Links in Abiotic and Biotic Stress Responses in Plants: A Perspective toward Secondary Metabolic Engineering

Abstract: Plants employ a diversified array of defense activities when they encounter stress. Continuous activation of defense pathways that were induced by mutation or altered expression of disease resistance genes and mRNA surveillance mechanisms develop abnormal phenotypes. These plants show continuous defense genes’ expression, reduced growth, and also manifest tissue damage by apoptosis. These macroscopic abrasions appear even in the absence of the pathogen and can be attributed to a condition known as autoimmunity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 105 publications
(96 reference statements)
0
5
0
Order By: Relevance
“…Furthermore, physiological and biochemical analyses showed that the pearl millet plants under salt stress exhibited reduced growth rates, decreased chlorophyll content, increased electrolyte leakage, and higher levels of reactive oxygen species compared to the control group. 29 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, physiological and biochemical analyses showed that the pearl millet plants under salt stress exhibited reduced growth rates, decreased chlorophyll content, increased electrolyte leakage, and higher levels of reactive oxygen species compared to the control group. 29 …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, physiological and biochemical analyses showed that the pearl millet plants under salt stress exhibited reduced growth rates, decreased chlorophyll content, increased electrolyte leakage, and higher levels of reactive oxygen species compared to the control group. 29 The study results (Figures 9-11) reveal four common abiotic KEGG pathways that play vital roles in pearl millet's response to salt and heat stress: phenylpropanoid biosynthesis, photosynthesis (antenna proteins), photosynthesis, and plant hormone signal transduction. These metabolic pathways are believed to be essential in the mechanism of cross-tolerance.…”
Section: Heat and Salt Stress Impact On Gene Expression And Adaptive ...mentioning
confidence: 99%
“…Plant SMs are often linked with the plant's resistance to environmental stressors [26,[44][45][46][47][48]. Phenols, flavonoids specifically, can act in various roles: as antioxidants [44,45], antimicrobials [45], etc.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, inducible defenses are activated immediately following plant tissue damage, whereas constitutive defenses are ubiquitously active prior to injury. In response to stress, plants may elicit defenses by hormone pathways and chemical signals, resulting in cross‐tolerance so that activation of one stress response leads to eliciting multiple responses to combat various types of stress (Perincherry et al, 2021). An example of cross‐tolerance is demonstrated in the mechanical wounded tomato plant showing increased salt tolerance that involved both systemin and the jasmonic acid (JA) biosynthetic pathway (Capiati et al, 2006).…”
Section: Introductionmentioning
confidence: 99%